The Crisis of Democratic Capitalism - Elmendorf, Doug (Journal of Economic Literature, 2024)
Doug Elmendorf of Harvard University reviews “The Crisis of Democratic Capitalism” by Martin Wolf. The EconLit abstract of this book begins: “Promotes the argument that economic disappointment is one of the chief explanations for the rise of left- and right-wing populism in high-income democracies, focusing on what can be done to restore the relationship between capitalism and democracy.”